Deletion of Specific Sphingolipids in Distinct Neurons Improves Spatial Memory in a Mouse Model of Alzheimer’s Disease - Herzer, Silke; Hagan, Cassidy; von Gerichten, Johanna; Dieterle, Vanessa; Munteanu, Bogdan; Sandhoff, Roger; Hopf, Carsten; Nordström, Viola (Frontiers in Molecular Neuroscience, 2018)
Alzheimer’s disease (AD) is characterized by progressive neurodegeneration and a concomitant loss of synapses and cognitive abilities. Recently, we have proposed that an alteration of neuronal membrane lipid microdomains increases neuronal resistance towards amyloid-β stress in cultured neurons and protects from neurodegeneration in a mouse model of AD. Lipid microdomains are highly enriched in a specific subclass of glycosphingolipids, termed gangliosides. The enzyme glucosylceramide synthase (GCS) catalyzes the rate-limiting step in the biosynthesis of these gangliosides. The present work now demonstrates that genetic GCS deletion in subsets of adult forebrain neurons significantly improves the spatial memory and counteracts the loss of dendritic spines in the hippocampal dentate gyrus of 5x familial AD mice (5xFAD//Ugcgf/f//Thy1-CreERT2//EYFP mice), when compared to 5xFAD//Ugcgf/f littermates (5xFAD mice). Aberrantly activated glial cells and their expression of pro-inflammatory cytokines have emerged as the major culprits for synaptic loss in AD. Typically, astrocytic activation is accompanied by a thickening of astrocytic processes, which impairs astrocytic support for neuronal synapses. In contrast to 5xFAD mice, 5xFAD//Ugcgf/f//Thy1-CreERT2//EYFP display a less pronounced thickening of astrocytic processes and a lower expression of TNF-α and IL1-α in the hippocampus. Thus, this work further emphasizes that GCS inhibition may constitute a potential therapeutic target against AD.